Comparison of broad-spectrum antibiotics and narrow-spectrum antibiotics in the treatment of lower extremity cellulitis - Almulhim, Abdulaziz Saleh; Alotaibi, Fawaz M. (International Journal of Health Sciences, 2018)
Objective: Cellulitis is a commonly encountered medical illness and is most frequently caused by Group A β-hemolytic Streptococcus species and Staphylococcus aureus. The purpose of this study was to compare clinical outcomes of patients with lower extremity cellulitis treated with broad-spectrum and narrow-spectrum antibiotics. Methods: This was a retrospective cohort study conducted in a community tertiary hospital between January 2016 and May 2016. Patients were included if they were diagnosed with uncomplicated non-purulent lower extremity cellulitis. Patients were divided into two groups: Individuals receiving narrow-spectrum antibiotics or receiving broad-spectrum antibiotics. Logistic regression analysis was used to estimate the odds ratio of repeat visit between the groups. Results: A total of 599 patients with uncomplicated cellulitis were identified; of which 120 were included in the study (93 in narrow-spectrum arm and 27 in broad-spectrum arm). Repeat visit due to cellulitis was similar in both Groups 1 (4%) and 3 (3%) (P = 0.89) in the broad-spectrum arm and narrow-spectrum arm, respectively. Conclusion: Broad-spectrum antibiotic use in uncomplicated cellulitis was common and unjustified given the results of our study. Implementation of clinical practice guidelines is recommended in limiting broad-spectrum antibiotics use in such population.